Multiplicity and concentration of solutions for Kirchhoff equations with exponential growth - Xueqi Sun; Yongqiang Fu; Sihua Liang (Bulletin of Mathematical Sciences)
In this paper, we deal with fractional [Formula: see text]-Laplace Kirchhoff equations with exponential growth of the form 𝜀ps(a + b[u] s,pp)(−Δ) psu + Z(x)|u|p−2u = h(u)in ℝN, where [Formula: see text] is a positive parameter, [Formula: see text], [Formula: see text] and [Formula: see text]. Under some appropriate conditions for the nonlinear function [Formula: see text] and potential function [Formula: see text], and with the help of penalization method and Lyusternik–Schnirelmann theory, we establish the existence, multiplicity and concentration of solutions. To some extent, we fill in the gaps in [W. Chen and H. Pan, Multiplicity and concentration of solutions for a fractional [Formula: see text]-Kirchhoff type equation, Discrete Contin. Dyn. Syst. 43 (2023) 2576–2607; G. Figueiredo and J. Santos, Multiplicity and concentration behavior of positive solutions for a Schrödinger–Kirchhoff type problem via penalization method, ESAIM Control Optim. Calc. Var. 20 (2014) 389–415; X. He and W. Zou, Existence and concentration behavior of positive solutions for a Kirchhoff equation in [Formula: see text] J. Differential Equations 252 (2012) 1813–1834; J. Wang, L. Tian, J. Xu and F. Zhang, Multiplicity and concentration of positive solutions for a Kirchhoff type problem with critical growth, J. Differential Equations 253 (2012) 2314–2351].